PELAKSANAAN PEMBERIAN REWARD DAN PUNISHMENT DALAM PEMBELAJARAN PAI DI SMA NEGERI 13 MAKASSAR - R, Rusdianto; Alang, Sattu; Rahman, Ulfiani (Inspiratif Pendidikan, 2021)
This study aims to understand the process of giving rewards and punishments in Islamic education learning at SMA Negeri 13 Makassar. This type of research is a qualitative research with a phenomenological approach. Sources of research data are the vice principal, teachers and students. The data methods used were interviews, observation and documentation. The technique of processing and analyzing data is carried out in three stages, namely: data reduction, data presentation, and drawing conclusions. These results indicate that the awarding at SMA Negeri 13 Makassar is mostly in the form of praise and added grades, while for the punishment varies in form, some punishments are given in the form of adding assignments, offering warnings, to involving parents. However, most forms of punishment involve additional duties. Supporting factors that provide rewards at SMA Negeri 13 Makassar are the authority of teachers in organizing the reward, the support of the school and parents and the motivation of students. Supporting factors are namely the support of the school and parents and the awareness of students. Inhibiting factors for rewards are namely costs, environment and different levels of students. Penalty inhibiting factors are based on the attention of parents, the existence of human rights and the diverse character of students. The results of the researcher’s analysis are offering rewards and punishments that can increase students’ learning motivation, student learning achievement and can improve student behavior.